THE ROLE OF MORPHONOLOGY IN MORPHOLOGICAL LANGUAGE TYPOLOGY - Xasanov Maxmudjan Abduraxmanovich (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
This paper examines the role of morphonology—the interface between phonology and morphology—in the morphological typology of languages. By analyzing how morphonological processes shape word forms in agglutinative, fusional, and isolating languages, the paper underscores morphonology’s importance in both synchronic analysis and typological classification. The study draws from cross-linguistic examples and theoretical insights to argue that morphonology plays a crucial role in explaining phonological alternations conditioned by morphological environments.